Facial wound due to canine bite in an old man - Antonio Gaspar Díaz Ramos; Darselys Rivero Linares; Noelia de Jesús Eduarzín Curet (Centro Provincial de Información de Ciencias Médicas, 2021)
The case report of a 73 years old man is presented. He was assisted in the Emergency Service of Enrique Cabrera Cossío Teaching General Hospital in Havana city, due to a dog bite in his face, in the right supraciliary region, that caused him a lacerated wound, with considerable loss of soft tissues, abundant bleeding and pain. After making antisepsis of the area and prevention with antibiotics, the surgical procedure was quickly practiced that consisted on debridement of the wound and reconstruction of the defect through primary plasty with technique of advance and rotation local flaps, that allowed a favorable clinical course in the patient, both cosmetic and functional.